Ten years of visual field change in people living with diabetes: A prospective longitudinal study - Karl-Johan Hellgren; Boel Bengtsson (PLoS ONE, 2025)
Background A better characterization of diabetic retinopathy (DR) may be helpful to monitor early disease, predict progression of DR, and to evaluate new treatment strategies. Visual function has been suggested to complement the assessment of microvascular lesions in DR but needs to be evaluated in longitudinal studies. Objectives This prospective longitudinal cohort study investigated whether early visual field deterioration in diabetes is associated with change in DR, and whether known risk factors as diabetes duration and glycated A1c (HbA1c) affect the visual field. Methods People living with diabetes, 18 to 75 years of age, were consecutively recruited from the local DR screening program. Individuals with eye diseases other than DR that could affect the visual field, and those who had received previous local eye treatment for DR, could not be included. Participants who had completed a five-year follow-up were re-examined after nine and ten years from baseline. The most important outcome was deterioration in series of visual fields as determined by an experimental model tailored for people living with diabetes. Stages of DR were evaluated according to the Early Treatment Diabetic Retinopathy Study (ETDRS) scale, and glycemic control by measurement of HbA1c. Results Fifty-six participants (median age 69 years at the last visit, 35 males) completed 608 out of 616 scheduled visits during ten years of follow-up. Progression and regression of DR occurred most often between no (ETDRS level 10) and minimal (ETDRS level 20) DR. The number of deteriorated test points increased annually by 11% (95% CI: 6.9–15.3) and were not associated with change in DR but with higher levels of HbA1c. Conclusions Early deterioration of visual function occurred independently of DR and was associated with worse glycemic control, suggesting that the metabolic disturbances due to diabetes induced a primary deterioration of sensitivity in the visual field.